2023
DOI: 10.3390/cancers15143624
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell (HSC)-Independent Progenitors Are Susceptible to Mll-Af9-Induced Leukemic Transformation

Cristiana Barone,
Roberto Orsenigo,
Anna Cazzola
et al.

Abstract: Infant acute myeloid leukemia (AML) is a heterogeneous disease, genetically distinct from its adult counterpart. Chromosomal translocations involving the KMT2A gene (MLL) are especially common in affected infants of less than 1 year of age, and are associated with a dismal prognosis. While these rearrangements are likely to arise in utero, the cell of origin has not been conclusively identified. This knowledge could lead to a better understanding of the biology of the disease and support the identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In addition, we observed that the HMX3 locus was epigenetically inactive (so very likely not bound by the activator KMT2A::MLLT3) in a MECOM + KMT2A::MLLT3 AML case. These differences might be attributed by different types of stem cells being transformed in children and young adults versus older cases [43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed that the HMX3 locus was epigenetically inactive (so very likely not bound by the activator KMT2A::MLLT3) in a MECOM + KMT2A::MLLT3 AML case. These differences might be attributed by different types of stem cells being transformed in children and young adults versus older cases [43][44][45] .…”
Section: Discussionmentioning
confidence: 99%